Pengembangan Standar Operasional Prosedur (SOP) Kas Kecil untuk Meningkatkan Transparansi dan Akuntabilitas Keuangan di Jemaat GMIM Getsemani Sumompo Wilayah Manado Utara Dua - Lintong, Jerry Sonny; Walukow, Ivoletti Merlina; Langi, Treesje A. C.; Paendong, Yelly Sj.; Rengku, Jeffry Otniel (EDUPEDIA Publisher, 2025)
This community service activity was conducted at the GMIM Getsemani Sumompo Congregation in response to the lack of a written Standard Operating Procedure (SOP) for managing the congregation's petty cash. Unsystematically documented daily operational fund management risks recording errors and weak accountability. Through a participatory approach, this activity involved financial managers, with the following stages: problem identification, outreach, SOP development, testing, and evaluation. Observations and interviews revealed that petty cash record keeping was not yet standardized. A draft SOP was developed through a Focus Group Discussion (FGD) and covered several key components: fund requests, approvals, disbursements, recording, replenishment, and reporting. Pre- and post-tests showed a 29% increase in financial managers' understanding. The two-month trial resulted in an 85% procedural compliance rate, exceeding the established target. This activity successfully produced an SOP document that can be effectively implemented and serves as a model for transparent and accountable petty cash management for other congregations within the Minahasa Evangelical Christian Church Synod. Keywords: Petty Cash SOP; accountability; church; internal control